Impact of the removal of the buccal fat pad on associated anatomical structures: a integrative review (Research, Society and Development, 2021)
This literature review aimed to study the complications resulting from the surgical removal of the buccal fat pad, seeking to understand the anatomical relationships between the structures involved in this procedure and to observe the main sequelae caused by traumatic injuries to these structures. The work was developed based on PRISMA protocols and guidelines, whose methodology involved a bibliographic survey of studies published in the last 10 years, found in the following databases in the health area: PubMed/Medline, Scopus, LILACS, SciELO and Cocrhane. It was found that the anatomical implications of structures related to the buccal fat pad are important to avoid the development of complications after the removal of the Bichat’s fat pad. These findings allow us to conclude that it is necessary to understand the impact that complications resulting from injuries to anatomical structures adjacent to the buccal fat pad can have on the quality of life of patients.